Witnessing Arbitrariness: Roncarelli v. Duplessis Fifty Years On - Liston, Mary (McGill Law Journal / Revue de droit de McGill, 2010)
In Canadian public law, Roncarelli v. Duplessis stands for the proposition that arbitrariness and the rule of law are conceptually antithetical values. This article examines multiple forms of arbitrariness in Roncarelli, going beyond the usual focus on discretionary power arbitrarily exercised by the executive branch of government.A close reading of the case brings to the surface other forms of arbitrariness, notably under-acknowledged forms of judicial arbitrariness. Repositioning the case in its social and political context provides an alternative vantage point from which the core conceptual content can be enlarged and the case’s normative import better gleaned. The article argues that such a repositioning illuminates how legal actors attempt to constrain arbitrariness within the activity of judging. Reason-giving appears as one significant rule of law practice that can counter institutionalized arbitrariness by seeking to ensure that decision makers throughout the state are attuned to the demands of legality, can be held to account, and are committed to upholding good government.